An approach to determining, delivering, and assessing essential course content in a medical human anatomy course - McNamara, John P.; Nolan, Michael F. (Clinical anatomy (New York, N.Y.), 2022)
Learning objectives typically indicate subject matter judged to be important or that represents essential material to be learned during a course. We report here on our efforts to identify essential course content and determine our effectiveness teaching and assessing this content in our preclinical human anatomy course. Using a consensus driven approach, we identified anatomical structures, relationships, and functional concepts judged to represent essential material in our unit on the thorax that students were expected to be familiar with. We then determined performance on specific examination questions that focused directly on the essential material. Thirty‐seven of 48 students (77%) correctly answered all 34 of 51 questions that directly focused on content we defined as essential. The remaining 11 students answered the majority of these questions correctly. The overall mean score was 86% (range 61%–98%). Our review of student performance on the End of Block thorax examination confirmed our belief that we were successful in helping students learn material we defined as essential. We found the process described here to be helpful in defining essential content and for helping focus and improve medical education and learning assessment based on that material. We believe the idea of defining essential content that can be efficiently taught and effectively learned within a proscribed period of time is an important and necessary objective. We believe the approach used here might be successfully utilized in other programs in efforts aimed at quality improvement.